2020
DOI: 10.48550/arxiv.2002.07698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of Cycles in Polyhedra I: The Isolation Lemma

Abstract: A cycle C of a graph G is isolating if every component of G−V (C) is a single vertex. We show that isolating cycles in polyhedral graphs can be extended to larger ones:) implies an isolating cycle C of larger length that contains V (C). By "hopping" iteratively to such larger cycles, we obtain a powerful and very general inductive motor for proving long cycles and computing them (we will give an algorithm with quadratic running time). This is the first step towards the so far elusive quest of finding a univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…For example, the authors [10] showed that if G is an essentially 4-connected planar graph on n vertices, then it has a cycle of length at least (2n + 6)/3 and this bound is best possible. This result was independently proved by Kessler and Schmidt [3] using a different method. As an immediate corollary of Theorem 1.1, we have the following The bound on |C| is tight with K 4 as an example.…”
Section: Discussionmentioning
confidence: 69%
“…For example, the authors [10] showed that if G is an essentially 4-connected planar graph on n vertices, then it has a cycle of length at least (2n + 6)/3 and this bound is best possible. This result was independently proved by Kessler and Schmidt [3] using a different method. As an immediate corollary of Theorem 1.1, we have the following The bound on |C| is tight with K 4 as an example.…”
Section: Discussionmentioning
confidence: 69%